2013
DOI: 10.1186/1472-6831-13-30
|View full text |Cite
|
Sign up to set email alerts
|

Socio-behavioural factors and early childhood caries: a cross-sectional study of preschool children in central Trinidad

Abstract: BackgroundEarly childhood caries (ECC) is a public health problem due to its impact on children’s health, development and well being. Little is known about early childhood oral health in the West Indies or the influence of social and behavioural factors on the prevalence and severity of early childhood caries in this preschool population. The aims of this study were to describe the prevalence and severity of ECC in preschool children in a region of central Trinidad and to explore its relationship with social a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 23 publications
4
35
0
3
Order By: Relevance
“…ECC was found in 74.2% of the enrolled children and S-ECC was diagnosed in 40.1%. The prevalence and severity of dental caries in these children increased with age, probably because of longer exposure to environmental cariogenic challenges, as reported in other studies [3, 32]. The caries prevalence in this study was high compared with that in other populations around the world [4, 7, 22, 33, 34].…”
Section: Discussionsupporting
confidence: 75%
“…ECC was found in 74.2% of the enrolled children and S-ECC was diagnosed in 40.1%. The prevalence and severity of dental caries in these children increased with age, probably because of longer exposure to environmental cariogenic challenges, as reported in other studies [3, 32]. The caries prevalence in this study was high compared with that in other populations around the world [4, 7, 22, 33, 34].…”
Section: Discussionsupporting
confidence: 75%
“…Of these children, 50.2% were male, with an age range of 3 to 5 years-old and mean age of 3.7 years (sd 0.67). Full results for visible caries experience have been reported previously [10]. Socio-demographic characteristic for parents/primary caregivers, together with information on ECOHIS and dmft for those children who completed the oral health assessment, are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In central Trinidad, the prevalence of ECC among 251 preschool children was reported as 29.1% with the majority of this being untreated, decayed teeth and 12% of children were in need of urgent care or referral [10]. Affordability and access to dental care for people from lower socioeconomic groups and those living in rural locations is a challenge in Trinidad and Tobago as most of the county’s registered dentists work in private practices, generally clustered in urban centers.…”
Section: Introductionmentioning
confidence: 99%
“…However, the percentage of those capable of detecting decayed primary teeth was rather low (65%), so it is necessary for them to attend special training sessions in cooperation with professionals. Previous studies showed that primary and secondary caregivers sought professional dental care mainly for children with severe symptoms of tooth decay (35,40,41). These results indicate that caregivers generally make inadequate efforts to monitor children's dental health status, promote and implement preventive programs related to EEC.…”
Section: Discussionmentioning
confidence: 65%